Preparation method of gel semi-solid battery and gel semi-solid battery

By solving the problem of uneven gel dispersing and incomplete solidification through the pre -gel monomer in the dry method of gel semi -solid battery and combined with the in situ aggregation solidification technology, it has achieved higher electrochemical properties and safety performance.

CN119361841APending Publication Date: 2025-01-24XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411513201.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing gel semi-solid battery preparation methods can easily lead to uneven dispersion of gels, poor contact with the gel and active substances, incomplete curing, and affect battery performance.

Method used

The drying electrode technology is pre -mixed into the gel monomer in the positive and negative pole films, combined with the in -situ aggregation curing technology, and the prefabrication of gel electrolyte in the stem core and heating and solidification can be improved. CICS uniformity and close contact with active materials.

Benefits of technology

Improve the overall electrical performance of gel semi -solid batteries, enhance the conductivity of gel and active materials, and improve electrochemical properties and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361841A_ABST
    Figure CN119361841A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a gel semi-solid battery and the gel semi-solid battery, and belongs to the technical field of battery materials. The preparation method comprises the following steps: pre-mixing a gel monomer into a positive pole piece and a negative pole piece by adopting a dry electrode technology, then assembling the positive pole piece, the negative pole piece and a diaphragm into a dry battery cell, injecting a gel electrolyte prepolymer prepared from the gel monomer, an electrolyte, an initiator and the like into the dry battery cell, and standing and infiltrating; and heating and carrying out in-situ polymerization curing to obtain the gel semi-solid battery. According to the preparation method, a dry-method electrode technology and an in-situ curing technology are combined, on one hand, the curing uniformity of the gel electrolyte prepolymer is improved, on the other hand, it can be guaranteed that the cured gel electrolyte prepolymer makes closer contact with active material particles, the conductivity of gel and the active material is improved, and the conductivity of the active material is improved. Therefore, the overall electrical performance of the semi-solid battery is improved. The invention also provides a gel semi-solid battery which is prepared by the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a preparation method of a gel semi-solid battery and a gel semi-solid battery. Background Art

[0002] Most of the existing gel semi-solid batteries are prepared by in-situ polymerization, and some of the preparation methods have been disclosed in patents, literature, etc. For example, the Chinese patent application with publication number CN116247288 A discloses a method for preparing a semi-solid battery, which can be specifically prepared by first mixing the electrolyte, gel monomer, initiator, etc., and then injecting them into the battery cell, and finally curing them by high temperature or other methods; for example, the preparation methods disclosed in the Chinese patent applications with publication numbers CN115548456A and CN117039180 are to inject the electrolyte, gel monomer and initiator into the battery cell in different orders, and then perform in-situ polymerization.

[0003] However, the above preparation method easily leads to uneven dispersion of the gel, and it is difficult for the gel to maintain good contact with the active material in the electrode, and the solidification cannot be complete, thus affecting the overall performance of the battery.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the shortcomings and defects of the prior art, the present invention aims to provide a method for preparing a gel semi-solid battery and a gel semi-solid battery prepared by the preparation method.

[0006] In order to achieve the above purpose, the following technical solutions are adopted:

[0007] The first object of the present invention is to provide a method for preparing a gel semi-solid battery, comprising the following steps:

[0008] (a) mixing a positive electrode active material, a positive electrode conductive agent, a gel monomer, an initiator and a positive electrode binder to form a positive electrode material, and then preparing a dry positive electrode sheet by using a dry electrode technology;

[0009] The negative electrode active material, the negative electrode conductive agent, the gel monomer, the initiator and the negative electrode binder are mixed to form a negative electrode material, and then the negative electrode material is made into a dry negative electrode sheet by a dry electrode technology;

[0010] (b) providing a gel electrolyte prepolymer formed by mixing a gel monomer, an initiator and an electrolyte;

[0011] (c) Assembling the dry-process positive electrode plate and the dry-process negative electrode plate obtained in step (a) with a separator into a dry battery cell, injecting the gel electrolyte prepolymer obtained in step (b) into the dry battery cell and allowing it to stand for infiltration, and then heating for in-situ polymerization and curing to obtain a gel semi-solid battery.

[0012] Furthermore, based on the above technical solution of the present invention, in step (a), the positive electrode active material, the positive electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a positive electrode mixture; then the positive electrode binder is added to the positive electrode mixture, sheared and mixed to obtain a positive electrode material; then the positive electrode material is rolled into a film, and compounded with a foil to obtain a dry-process positive electrode sheet.

[0013] Furthermore, based on the above technical solution of the present invention, in step (a), the negative electrode active material, the negative electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a negative electrode mixture; then the negative electrode binder is added to the negative electrode mixture, sheared and mixed to obtain a negative electrode material; then the negative electrode material is rolled into a film, and compounded with a foil to obtain a dry-process negative electrode sheet.

[0014] Further, on the basis of the above technical solution of the present invention, in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer, the gel monomer is a carbonate or acrylate organic reaction monomer, preferably including diallyl carbonate, propane trimethylol triacrylate, butyl methacrylate, methyl methacrylate, triethylene glycol dimethyl diacrylate, pentaerythritol tetraacrylate, pentaerythritol hexaacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, 2-bromoethyl acrylate, hydroxypropyl acrylate, Any one of isostearyl acrylate, isobutyl methacrylate, 4-hydroxybutyl acrylate, tributyltin acrylate, propane-1,3-diyl diacrylate, 4-ethylphenyl acrylate, hydroxyethyl acrylate, hydroxypentabromophenyl methacrylate, pentabromophenyl acrylate, 6-bromo-1-hexyl acrylate, 2-bromoethyl acrylate, 2-chloroethyl methacrylate, 11-undecylphosphonate, tributyltin acrylate or 2-(perfluorobutyl)ethyl acrylate, or any combination of two or more thereof;

[0015] And / or, in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer, the initiator includes an azo initiator or a peroxide initiator, preferably including at least one of azobisisobutyronitrile, diisopropylbenzene peroxide or dibenzoyl peroxide.

[0016] Further, based on the above technical solution of the present invention, the positive electrode active material includes at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide;

[0017] and / or, the negative electrode active material comprises at least one of graphite, silicon carbon, silicon oxygen or hard carbon;

[0018] And / or, the positive electrode conductive agent and the negative electrode conductive agent are independently selected from at least one of Ketjen black, carbon nanotubes, two-dimensional transition metal carbon / nitride, acetylene black, Super P or graphene;

[0019] And / or, the positive electrode binder and the negative electrode binder are independently selected from at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose or polyethylene oxide; preferably, the negative electrode binder includes polytetrafluoroethylene, sodium carboxymethyl cellulose and polyethylene oxide.

[0020] Furthermore, based on the above technical solution of the present invention, taking the mass fraction of the positive electrode material as 100%, the positive electrode material includes the following components in mass fractions: 85-95% positive electrode active material, 0.5-1.5% positive electrode conductor, 1-10% gel monomer, 0.05-1% initiator and 0.5-5% positive electrode binder.

[0021] Furthermore, based on the above technical solution of the present invention, taking the mass fraction of the negative electrode material as 100%, the negative electrode material includes the following components in mass fractions: 85-95% of negative electrode active material, 0.5-1.5% of negative electrode conductor, 2-10% of gel monomer, 0.2-1% of initiator and 0.5-5% of negative electrode binder.

[0022] Further, based on the above technical solution of the present invention, in step (b), gel monomer and initiator are added to the electrolyte and mixed evenly to obtain gel electrolyte prepolymer;

[0023] And / or, in step (b), based on the mass fraction of the gel electrolyte prepolymer being 100%, the gel electrolyte prepolymer comprises the following components in mass fractions: 89-98.95% electrolyte, 1-10% gel monomer and 0.05-1% initiator.

[0024] Further, based on the above technical solution of the present invention, in step (c), the static soaking time is 12 to 48 hours, and the static soaking temperature is 25 to 45°C;

[0025] And / or, the in-situ polymerization curing temperature is 50-80° C., the pressure is 0.3 MPa-1 MPa, and the curing time is 2-24 hours.

[0026] The second object of the present invention is to provide a gel semi-solid battery, which is prepared by the preparation method of the gel semi-solid battery provided by the first object of the present invention.

[0027] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:

[0028] (1) The present invention provides a method for preparing a gel semi-solid battery, which uses dry electrode technology to pre-mix gel monomers into positive and negative electrode sheets, and then assembles the positive and negative electrode sheets and separators into dry cells, injects gel electrolyte prepolymers made of gel monomers, electrolytes, and initiators into the dry cells, and then allows them to stand for infiltration, and then heats them for in-situ polymerization and curing to obtain a gel semi-solid battery. The preparation method combines dry electrode technology with in-situ curing technology, which improves the uniformity of the curing of the gel electrolyte prepolymer on the one hand, and can ensure that the gel electrolyte prepolymer is in closer contact with the active material particles after curing, thereby improving the conductivity of the gel and the active material, thereby improving the overall electrical performance of the semi-solid battery.

[0029] (2) The present invention provides a gel semi-solid battery, which is prepared by the preparation method of the gel semi-solid battery. In view of the advantages of the preparation method provided by the present invention, the electrochemical performance of the gel semi-solid battery prepared by the preparation method is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Ultrasonic test diagrams of the gel semi-solid battery cells prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0031] Figure 2 The charging DC internal resistance curves of the gel semi-solid batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at different SOCs are shown;

[0032] Figure 3 The discharge DC internal resistance curves of the gel semi-solid batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at different SOCs;

[0033] Figure 4 The charging performance curves of the gel semi-solid batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at different rates are shown;

[0034] Figure 5 The discharge performance curves of the gel semi-solid batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at different rates;

[0035] Figure 6 The graph is a cycle performance curve of the gel semi-solid battery cell prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention at a 1C rate. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0037] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0038] According to a first aspect of the present invention, there is provided a method for preparing a gel semi-solid battery, comprising the following steps:

[0039] (a) mixing a positive electrode active material, a positive electrode conductive agent, a gel monomer, an initiator and a positive electrode binder to form a positive electrode material, and then preparing a dry positive electrode sheet by using a dry electrode technology;

[0040] The negative electrode active material, the negative electrode conductive agent, the gel monomer, the initiator and the negative electrode binder are mixed to form a negative electrode material, and then the negative electrode material is made into a dry negative electrode sheet by a dry electrode technology;

[0041] (b) providing a gel electrolyte prepolymer formed by mixing a gel monomer, an initiator and an electrolyte;

[0042] (c) Assembling the dry-process positive electrode plate and the dry-process negative electrode plate obtained in step (a) with a separator into a dry battery cell, injecting the gel electrolyte prepolymer obtained in step (b) into the dry battery cell and allowing it to stand for infiltration, and then heating for in-situ polymerization and curing to obtain a gel semi-solid battery.

[0043] Specifically, in step (a), compared with directly injecting the gel electrolyte prepolymer into the dry cell (without premixing the gel monomer into the electrode), premixing the gel monomer into the electrode can improve the uniformity of the gel electrolyte curing, making the in-situ curing more complete, which will greatly improve the performance of the battery.

[0044] When premixing the gel monomer into the electrode, the inventors have found through extensive practice that the ratio of the amount of gel monomer in the electrode to the content of gel monomer in the gel electrolyte prepolymer is preferably consistent, so as to ensure that the performance of the battery after curing can remain consistent. If the gel monomer is premixed into the electrode by a wet method, most gel monomers have restrictions on solvents, and the gel monomer will be lost as the solvent evaporates when the electrode is baked, resulting in the gel monomer content in the electrode being less than the gel electrolyte prepolymer, causing uneven dispersion of the gel electrolyte after curing, thereby affecting the overall performance of the battery. The use of dry electrode technology to premix the gel monomer into the electrode can avoid the loss of gel monomer volatilization due to high-temperature baking of the electrode, resulting in the gel monomer content in the electrode being less than the gel electrolyte prepolymer, thereby causing the problem of uneven dispersion of the gel electrolyte after curing.

[0045] In step (b), gel monomer, initiator and electrolyte are mixed to prepare gel electrolyte prepolymer.

[0046] In step (c), the gel semi-solid battery is prepared by in-situ polymerization and curing of the gel electrolyte prepolymer.

[0047] The present invention combines dry electrode technology with in-situ curing technology. By pre-mixing gel monomers into the electrode, on the one hand, the uniformity of the curing of the gel electrolyte prepolymer is improved, and on the other hand, it can ensure that the gel electrolyte prepolymer is in closer contact with the active material particles after curing, thereby improving the conductivity of the gel and the active material, thereby improving the overall electrical performance of the semi-solid battery.

[0048] As an optional implementation of the technical solution of the present invention, in step (a), the positive electrode active material, the positive electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a positive electrode mixture; then the positive electrode binder is added to the positive electrode mixture, sheared and mixed to obtain a positive electrode material; then the positive electrode material is rolled into a film, and compounded with a foil to obtain a dry-process positive electrode sheet.

[0049] As an optional implementation of the technical solution of the present invention, in step (a), the negative electrode active material, the negative electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a negative electrode mixture; then the negative electrode binder is added to the negative electrode mixture, sheared and mixed to obtain a negative electrode material; then the negative electrode material is rolled into a film, and compounded with a foil to obtain a dry-process negative electrode sheet.

[0050] The active material (positive electrode active material or negative electrode active material), the conductive agent (positive electrode conductive agent or negative electrode conductive agent), the gel monomer and the initiator are first mixed, and then the binder (positive electrode binder or negative electrode binder) is added. This allows the various materials to be mixed more evenly and the gel monomer to polymerize more fully during the subsequent in-situ curing.

[0051] In order to ensure that the reaction of the gel system is simpler and more complete and to reduce the occurrence of side reactions, the types of gel monomers used in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer are preferably the same. As an optional implementation of the technical solution of the present invention, in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer, the gel monomer is a carbonate or acrylate organic reaction monomer, preferably including diallyl carbonate, propane trimethylol triacrylate, butyl methacrylate, methyl methacrylate, triethylene glycol dimethyl diacrylate, pentaerythritol tetraacrylate, pentaerythritol hexaacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, 2-bromoethyl acrylate, hydroxypropyl acrylate, isostearyl alcohol, Any one of 1,3-diyl acrylate, isobutyl methacrylate, 4-hydroxybutyl acrylate, tributyltin acrylate, propane-1,3-diyl diacrylate, 4-ethylbenzene acrylate, hydroxyethyl acrylate, hydroxypentabromophenyl methacrylate, pentabromophenyl acrylate, 6-bromo-1-hexyl acrylate, 2-bromoethyl acrylate, 2-chloroethyl methacrylate, 11-undecylphosphonate, tributyltin acrylate or 2-(perfluorobutyl)ethyl acrylate, or any combination of two or more thereof.

[0052] As an optional implementation of the technical solution of the present invention, in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer, the initiator includes an azo initiator or a peroxide initiator, preferably including at least one of azobisisobutyronitrile, diisopropylbenzene peroxide or dibenzoyl peroxide.

[0053] By further limiting the specific types of gel monomers and initiators, the gel electrolyte after the in-situ polymerization reaction has better ionic conductivity.

[0054] The types of active materials, conductive agents and binders are not specifically limited and can be selected according to the actual battery system. As an optional implementation of the technical solution of the present invention, the positive electrode active material includes at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide.

[0055] As an optional implementation of the technical solution of the present invention, the negative electrode active material includes at least one of graphite, silicon carbon, silicon oxygen or hard carbon.

[0056] As an optional implementation of the technical solution of the present invention, the positive electrode conductive agent and the negative electrode conductive agent are independently selected from at least one of Ketjen black, carbon nanotubes, two-dimensional transition metal carbon / nitride, acetylene black, Super P or graphene.

[0057] Among them, two-dimensional transition metal carbon / nitrides (i.e., two-dimensional transition metal carbides and two-dimensional transition metal nitrides) are a class of highly conductive two-dimensional materials with rich surface functional groups, including Ti3C2, Ti2C, V2C, Cr3C2, Fe2C, Cr2N or Ti4N3, etc.

[0058] As an optional implementation of the technical solution of the present invention, the positive electrode binder and the negative electrode binder are independently selected from at least one of polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose or polyethylene oxide (PEO).

[0059] As a preferred implementation of the technical solution of the present invention, the negative electrode binder includes polytetrafluoroethylene, sodium carboxymethyl cellulose and polyethylene oxide.

[0060] Polytetrafluoroethylene is used as the main binder in the negative electrode binder, and sodium carboxymethyl cellulose and polyethylene oxide are used as auxiliary binders. Polyethylene oxide is added to the dry electrode as an auxiliary binder. On the one hand, polyethylene oxide, as a polymer electrolyte, can improve the ion conductivity of the electrode sheet. On the other hand, it can block the side reaction between polytetrafluoroethylene and lithium on the negative electrode side, thereby improving the initial efficiency of the battery.

[0061] As an optional implementation mode of the technical solution of the present invention, taking the mass fraction of the positive electrode material as 100%, the positive electrode material includes the following components in mass fractions: 85-95% of positive electrode active material, 0.5-1.5% of positive electrode conductor, 1-10% of gel monomer, 0.05-1% of initiator and 0.5-5% of positive electrode binder.

[0062] Unlike traditional positive electrode sheets, gel monomers and initiators are also added to the positive electrode sheets (positive electrode materials) of the present invention. The amount of gel monomer used affects the electrical properties and safety performance of the battery. If the mass fraction of the gel monomer is too high (higher than 10%), the ionic conductivity of the gel electrolyte after polymerization will be greatly reduced, the internal resistance of the battery cell will become larger, and the electrical performance of the battery will be greatly reduced. If the mass fraction of the gel monomer is too low (lower than 1%), the gel polymer formed by the reaction is too small to completely enclose the electrolyte, and free electrolyte will exist, reducing the safety of the battery. Therefore, the amount of gel monomer used is preferably within the specific numerical range specified in the present invention. Typical but non-restrictive mass fractions are 1%, 2%, 3%, 4%, 5%, 6%, 8% or 10% and the numerical range between any two points.

[0063] Similarly, the amount of initiator is also preferably limited to a certain range. If the mass fraction of the initiator is too high (higher than 1%), more free radicals are easily generated, which will cause excessive polymerization of the gel monomer and lead to uncontrollable reaction. If the mass fraction of the initiator is too low (lower than 0.05%), fewer free radicals are generated, which is not conducive to the polymerization of the gel monomer. Therefore, the typical but non-limiting mass fraction of the initiator is 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 0.9% or 1.0% and the numerical range between any two points.

[0064] The typical but non-limiting mass fraction of the positive active material is 85%, 86%, 88%, 90%, 92%, 94% or 95% and the numerical range between any two points; the typical but non-limiting mass fraction of the positive conductor is 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4% or 1.5% and the numerical range between any two points; the typical but non-limiting mass fraction of the positive binder is 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% and the numerical range between any two points.

[0065] As an optional implementation mode of the technical solution of the present invention, taking the mass fraction of the negative electrode material as 100%, the negative electrode material includes the following components in mass fractions: 85-95% of negative electrode active material, 0.5-1.5% of negative electrode conductor, 2-10% of gel monomer, 0.2-1% of initiator and 0.5-5% of negative electrode binder.

[0066] There are certain limits on the amount of gel monomer and initiator used in the positive electrode material, and there are also certain limits on the amount of gel monomer and initiator used in the negative electrode material. If the mass fraction of the gel monomer is too high (higher than 10%), the ionic conductivity of the gel electrolyte will be greatly reduced after polymerization, the internal resistance of the battery cell will increase, and the electrical performance of the battery will be greatly reduced. If the mass fraction of the gel monomer is too low (lower than 2%), the gel polymer formed by the reaction is too small to completely enclose the electrolyte, and there will be free electrolyte, which reduces the safety of the battery. Therefore, the amount of gel monomer is preferably within the specific numerical range specified in the present invention. The typical but non-restrictive mass fraction is 2%, 3%, 4%, 5%, 6%, 8% or 10% and the numerical range between any two points. If the mass fraction of the initiator is too high (higher than 1%), more free radicals will be generated, which will cause the gel monomer to over-polymerize and make the reaction uncontrollable. If the mass fraction of the initiator is too low (lower than 0.2%), fewer free radicals will be generated, which is not conducive to the polymerization of the gel monomer. Therefore, typical but non-limiting mass fractions of the initiator are 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 0.9% or 1.0% and numerical ranges between any two points.

[0067] Typical but non-limiting mass fractions of negative electrode active materials are 85%, 86%, 88%, 90%, 92%, 94% or 95% and the range of values ​​between any two points; typical but non-limiting mass fractions of negative electrode conductors are 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4% or 1.5% and the range of values ​​between any two points; typical but non-limiting mass fractions of negative electrode binders are 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% and the range of values ​​between any two points.

[0068] As an optional implementation of the technical solution of the present invention, in step (a), the components of the positive electrode material are weighed according to the ratio, put into a mixer and mixed evenly, and then fiberized into agglomerates by high-speed shearing. Then, the agglomerated mixture (positive electrode material) is rolled into a film by a roller press, and finally rolled together with the foil by a composite machine to prepare a dry-process electrode.

[0069] As an optional implementation of the technical solution of the present invention, in step (b), gel monomer and initiator are added to the electrolyte and mixed evenly to obtain gel electrolyte prepolymer (i.e., a mixture of gel monomer, initiator and electrolyte). It should be noted that the gel monomer will not be prepolymerized in this process.

[0070] Mix the above substances evenly in a glove box or dry room (dew point < -50°C, humidity less than 1%), and the ambient temperature must be ≤ 25°C.

[0071] As an optional implementation of the technical solution of the present invention, in step (b), based on the mass fraction of the gel electrolyte prepolymer being 100%, the gel electrolyte prepolymer includes the following components in mass fractions: 89-98.95% electrolyte, 1-10% gel monomer and 0.05-1% initiator.

[0072] It should be noted that the electrolyte is a commercially available general organic electrolyte, which is selected according to different positive and negative electrode systems. The typical but non-limiting mass fraction of the electrolyte is 89%, 90%, 90.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5% or 98.95%, etc., and the numerical range between any two points. The typical but non-limiting mass fraction of the gel monomer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and the numerical range between any two points. Typical but non-limiting mass fractions of the initiator are 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8% or 1%, etc. and numerical ranges between any two points.

[0073] By further limiting the amounts of gel monomer, electrolyte and initiator in the gel electrolyte prepolymer, the gel polymer formed after curing has higher ion conductivity and can well encapsulate the electrolyte without generating free electrolyte.

[0074] As an optional implementation of the technical solution of the present invention, in step (c), the static infiltration time is 12 to 48 hours, and the static infiltration temperature is 25 to 45°C.

[0075] Typical but non-limiting static immersion times are 12h, 15h, 18h, 20h, 24h, 28h, 30h, 34h, 36h, 40h, 42h, 45h or 48h, and the range of values ​​between any two points; typical but non-limiting static immersion temperatures are 25°C, 30°C, 35°C, 40°C or 45°C, and the range of values ​​between any two points.

[0076] The above-defined standing and soaking time and temperature are conducive to the gel electrolyte prepolymer being able to fully soak into the electrode.

[0077] As an optional implementation of the technical solution of the present invention, the in-situ polymerization curing temperature is 50 to 80° C., the pressure is 0.3 MPa to 1 MPa, and the curing time is 2 to 24 hours.

[0078] Typical but non-limiting in-situ polymerization curing temperatures are 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C and the range of values ​​between any two points; typical but non-limiting in-situ polymerization pressures are 0.3Mpa, 0.4Mpa, 0.5Mpa, 0.6Mpa, 0.8Mpa or 1.0Mpa and the range of values ​​between any two points; typical but non-limiting in-situ polymerization curing times are 2h, 4h, 6h, 8h, 10h, 12h, 15h, 18h, 20h, 22h or 24h and the range of values ​​between any two points.

[0079] Further limiting the in-situ polymerization curing conditions is beneficial to the complete curing of the gel electrolyte prepolymer.

[0080] According to a second aspect of the present invention, there is also provided a gel semi-solid battery, which is prepared by the preparation method of the gel semi-solid battery provided by the first aspect of the present invention.

[0081] In view of the advantages of the preparation method of the gel semi-solid battery provided by the present invention, the electrochemical performance and safety performance of the gel semi-solid battery prepared thereby are greatly improved.

[0082] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0083] Example 1

[0084] This embodiment provides a method for preparing a gel semi-solid battery, comprising the following steps:

[0085] (a) The positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP), carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly in a mass ratio of 94.3:0.5:1:2:0.2:2, and then pressed into a film (thickness of 180-220 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 150 μm dry-process positive electrode sheet;

[0086] The negative electrode active material graphite, the negative electrode conductive agent conductive carbon black (SP), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN), the negative electrode binder polytetrafluoroethylene (PTFE), the negative electrode binder polyethylene oxide (PEO), and the negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed uniformly in a mass ratio of 94:1:2:0.2:1.5:1.2:0.1, and then pressed into a film (thickness of 130-150 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 120 μm dry-process negative electrode sheet;

[0087] (b) mixing a commonly used electrolyte adapted to lithium iron phosphate@graphite system (dimethyl carbonate (DMC), propylene carbonate (PC), vinylene carbonate (VC), and lithium hexafluorophosphate in a mass ratio of 40:40:8:12), a gel monomer diallyl carbonate, and azobisisobutyronitrile (AIBN) in a mass ratio of 95:4.8:0.2 to uniformly dissolve the gel monomer and initiator in the electrolyte to obtain a gel electrolyte prepolymer;

[0088] (c) placing the dry-process positive electrode sheet and the dry-process negative electrode sheet and the separator group prepared in step (a) in a battery shell to assemble into a dry battery cell, injecting the gel electrolyte prepolymer prepared in step (b) into the dry battery cell at an injection coefficient of 2.5 g / Ah, and then pre-sealing and standing at room temperature for 24 hours, and then heating for in-situ polymerization and curing. The in-situ polymerization and curing temperature is 60°C, the pressure is 0.6 MPa, and the curing time is 12 hours. Finally, exhaust and final sealing are performed. After volume separation, a gel semi-solid battery is obtained.

[0089] Example 2

[0090] This embodiment provides a method for preparing a gel semi-solid battery, comprising the following steps:

[0091] (a) The positive electrode active material NCM811, the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly in a mass ratio of 94.8:0.5:0.5:2:0.2:2, and then pressed into a film (thickness of 200-250 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 180 μm dry-process positive electrode sheet;

[0092] The negative electrode active material graphite, the negative electrode conductive agent conductive carbon black (SP), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN), the negative electrode binder polytetrafluoroethylene (PTFE), the negative electrode binder polyethylene oxide (PEO), and the negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed uniformly in a mass ratio of 94:1:2:0.2:1.5:1.2:0.1, and then pressed into a film (thickness of 160-180 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 140 μm dry-process negative electrode sheet;

[0093] (b) A commonly used electrolyte adapted to a high nickel ternary@graphite system (the mass ratio of ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), propylene carbonate (PC), vinyl sulfate (DTD) and lithium hexafluorophosphate is 30:20:35:1.5:13.5), a gel monomer diallyl carbonate and azobisisobutyronitrile (AIBN) are uniformly stirred in a mass ratio of 95:4.8:0.2 to fully dissolve the gel monomer and initiator in the electrolyte to obtain a gel electrolyte prepolymer;

[0094] (c) placing the dry-process positive electrode sheet and the dry-process negative electrode sheet and the separator group prepared in step (a) in a battery shell to assemble into a dry battery cell, injecting the gel electrolyte prepolymer prepared in step (b) into the dry battery cell at an injection coefficient of 2.2 g / Ah, and then pre-sealing and standing at room temperature for 24 hours, and then heating for in-situ polymerization and curing. The in-situ polymerization and curing temperature is 60°C, the pressure is 0.6 MPa, and the curing time is 12 hours. Finally, exhaust and final sealing are performed, and after volume separation, a gel semi-solid battery is obtained.

[0095] Example 3

[0096] This embodiment provides a method for preparing a gel semi-solid battery, comprising the following steps:

[0097] (a) The positive electrode active material NCM811, the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly in a mass ratio of 94.8:0.5:0.5:2:0.2:2, and then pressed into a film (thickness of 200-250 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 180 μm dry-process positive electrode sheet;

[0098] First, graphite and silicon carbon are mixed and compounded in a mass ratio of 9:1 to obtain silicon carbon graphite negative electrode powder (gram capacity 500mAh / g), and then the negative electrode powder, negative electrode conductive agent conductive carbon black (SP), gel monomer diallyl carbonate, initiator azobisisobutyronitrile (AIBN), negative electrode binder polytetrafluoroethylene (PTFE), negative electrode binder polyethylene oxide (PEO), negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2:0.2:1.5:1.2:0.1, and then pressed into a film (thickness 160-180μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 140μm dry-process negative electrode sheet;

[0099] (b) A commonly used electrolyte adapted to the high nickel ternary@silicon carbon system (the mass ratio of ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), propylene carbonate (PC), vinyl sulfate (DTD), lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide is 30:20:35:1.5:10:3.5), a gel monomer diallyl carbonate and azobisisobutyronitrile (AIBN) are stirred evenly in a mass ratio of 95:4.8:0.2 to fully dissolve the gel monomer and initiator in the electrolyte to obtain a gel electrolyte prepolymer;

[0100] (c) placing the dry-process positive electrode sheet and the dry-process negative electrode sheet and the separator group prepared in step (a) in a battery shell to assemble into a dry battery cell, injecting the gel electrolyte prepolymer prepared in step (b) into the dry battery cell at an injection coefficient of 2.2 g / Ah, and then pre-sealing and standing at room temperature for 24 hours, and then heating for in-situ polymerization and curing. The in-situ polymerization and curing temperature is 60°C, the pressure is 0.6 MPa, and the curing time is 12 hours. Finally, exhaust and final sealing are performed, and after volume separation, a gel semi-solid battery is obtained.

[0101] Example 4

[0102] This embodiment provides a method for preparing a gel semi-solid battery, comprising the following steps:

[0103] (a) The positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer propane trimethylol triacrylate (TMPTA), the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly in a mass ratio of 94.3:0.5:1:2:0.2:2, and then pressed into a film (thickness of 160-180 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 150 μm dry-process positive electrode sheet;

[0104] The negative electrode active material graphite, the negative electrode conductive agent conductive carbon black (SP), the gel monomer propane trimethylol triacrylate (TMPTA), the initiator azobisisobutyronitrile (AIBN), the negative electrode binder polytetrafluoroethylene (PTFE), the negative electrode binder polyethylene oxide (PEO), and the negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed uniformly in a mass ratio of 94:1:2:0.2:1.5:1.2:0.1, and then pressed into a film (thickness of 130-150 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 120 μm dry-process negative electrode sheet;

[0105] (b) a commonly used electrolyte adapted to lithium iron phosphate@graphite system (dimethyl carbonate (DMC), propylene carbonate (PC), vinylene carbonate (VC), lithium hexafluorophosphate in a mass ratio of 40:40:8:12), a gel monomer trimethylol propane triacrylate (TMPTA), and azobisisobutyronitrile (AIBN) in a mass ratio of 95:4.8:0.2 are stirred evenly to fully dissolve the gel monomer and initiator in the electrolyte to obtain a gel electrolyte prepolymer;

[0106] (c) placing the dry-process positive electrode sheet and the dry-process negative electrode sheet and the separator group prepared in step (a) in a battery shell to assemble into a dry battery cell, injecting the gel electrolyte prepolymer prepared in step (b) into the dry battery cell at an injection coefficient of 2.5 g / Ah, and then pre-sealing and standing at room temperature for 24 hours, and then heating for in-situ polymerization and curing. The in-situ polymerization and curing temperature is 50°C, the pressure is 0.6 MPa, and the curing time is 4 hours. Finally, exhaust and final sealing are performed. After volume separation, a gel semi-solid battery is obtained.

[0107] Example 5

[0108] This embodiment provides a method for preparing a gel semi-solid battery. The difference from Example 1 is that the type of gel monomer used is methyl methacrylate, and the in-situ polymerization curing temperature of step (c) is 60°C, the pressure is 0.5 MPa, and the curing time is 2 hours. The remaining raw materials, amounts and preparation methods are the same as those in Example 1.

[0109] Example 6

[0110] This embodiment provides a method for preparing a gel semi-solid battery. The difference from Example 2 is that the type of gel monomer used is trimethylolpropane triacrylate, and the in-situ polymerization curing temperature of step (c) is 60°C, the pressure is 0.5 MPa, and the curing time is 5 hours. The remaining raw materials, amounts and preparation methods are the same as those in Example 2.

[0111] Example 7

[0112] The present embodiment provides a preparation method of a gel semi-solid battery, which is different from the embodiment 1 in that the mass fraction of the gel monomer used in step (a) is 10%, and the mass fraction of the positive electrode active material lithium iron phosphate (LFP) is 86.3%, that is, the positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are uniformly mixed in a mass ratio of 86.3:0.5:1:10:0.2:2, and the remaining raw materials, amounts and preparation methods are the same as those in the embodiment 1.

[0113] Example 8

[0114] The present embodiment provides a preparation method of a gel semi-solid battery, which is different from the embodiment 1 in that the mass fraction of the gel monomer used in step (a) is 10.5%, and the mass fraction of the positive electrode active material lithium iron phosphate (LFP) is 85.8%, that is, the positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are uniformly mixed in a mass ratio of 85.8:0.5:1:10.5:0.2:2, and the remaining raw materials, amounts and preparation methods are the same as those in the embodiment 1.

[0115] Example 9

[0116] The present embodiment provides a preparation method of a gel semi-solid battery, which is different from the embodiment 1 in that the mass fraction of the gel monomer used in step (a) is 0.5%, and the mass fraction of the positive electrode active material lithium iron phosphate (LFP) is 95.8%, that is, the positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polytetrafluoroethylene (PTFE) are uniformly mixed in a mass ratio of 95.8:0.5:1:0.5:0.2:2, and the remaining raw materials, amounts and preparation methods are the same as those in the embodiment 1.

[0117] Example 10

[0118] This embodiment provides a method for preparing a gel semi-solid battery, which is different from Embodiment 1 in that the mass fraction of the gel monomer used in step (b) is 1%, that is, the mass ratio of the electrolyte, the gel monomer diallyl carbonate, and azobisisobutyronitrile (AIBN) is 98.8:1:0.2, and the remaining raw materials, amounts, and preparation methods are the same as those in Embodiment 1.

[0119] Embodiment 11

[0120] This embodiment provides a method for preparing a gel semi-solid battery, which is different from Example 1 in that the mass fraction of the gel monomer used in step (b) is 10%, that is, the mass ratio of the electrolyte, the gel monomer diallyl carbonate, and azobisisobutyronitrile (AIBN) is 89.8:10:0.2, and the remaining raw materials, amounts, and preparation methods are the same as those in Example 1.

[0121] Comparative Example 1

[0122] This comparative example provides a method for preparing a gel semi-solid battery. The difference from Example 1 is that the gel monomer and the initiator are not pre-mixed into the dry electrode in step (a). At the same time, in order to ensure that the ratio of the active materials in this comparative example is consistent with that in Example 1, and the content of the gel monomer in the entire gel semi-solid battery of this comparative example is as close as possible to that in Example 1, the amount of the gel monomer not added to the pole piece of this comparative example (i.e., equivalent to the amount of the gel monomer added to the pole piece of Example 1) is proportionally converted into the gel electrolyte prepolymer in step (b). The specific preparation method comprises the following steps:

[0123] (a) The positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP) and carbon nanofiber (VGCF) and the positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly at a mass ratio of 96.5:0.5:1:2, and then pressed into a film (thickness of 180-200 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 150 μm dry-process positive electrode sheet;

[0124] The negative electrode active material graphite, the negative electrode conductive agent conductive carbon black (SP), the negative electrode binder polytetrafluoroethylene (PTFE), the negative electrode binder polyethylene oxide (PEO), and the negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed uniformly at a mass ratio of 96.2:1:1.5:1.2:0.1, and then pressed into a film (thickness of 130-150 μm) by a roller press, and finally the electrode film is compounded with aluminum foil by calendaring to obtain a 120 μm dry-process negative electrode sheet;

[0125] (b) mixing a commonly used electrolyte adapted to lithium iron phosphate@graphite system (dimethyl carbonate (DMC), propylene carbonate (PC), vinylene carbonate (VC), and lithium hexafluorophosphate in a mass ratio of 40:40:8:12), a gel monomer diallyl carbonate, and azobisisobutyronitrile (AIBN) in a mass ratio of 94.2:5.6:0.2 to uniformly dissolve the gel monomer and initiator in the electrolyte to obtain a gel electrolyte prepolymer;

[0126] (c) placing the dry-process positive electrode sheet and the dry-process negative electrode sheet and the separator group prepared in step (a) in a battery shell to assemble into a dry battery cell, injecting the gel electrolyte prepolymer prepared in step (b) into the dry battery cell at an injection coefficient of 2.5 g / Ah, and then pre-sealing and standing at room temperature for 24 hours, and then heating for in-situ polymerization and curing. The in-situ polymerization and curing temperature is 60°C, the pressure is 0.6 MPa, and the curing time is 12 hours. Finally, exhaust and final sealing are performed. After volume separation, a gel semi-solid battery is obtained.

[0127] Comparative Example 2

[0128] This comparative example provides a method for preparing a gel semi-solid battery. The difference from Example 1 is that in step (a), the electrode is prepared by a wet method. The specific preparation method includes the following steps:

[0129] (a) The positive electrode active material lithium iron phosphate (LFP), the positive electrode conductive agent conductive carbon black (SP), carbon nanofiber (VGCF), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN) and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed uniformly at a mass ratio of 94.3:0.5:1:2:0.2:2, and then the solvent N-methylpyrrolidone (NMP) is added, and the wet method is used for homogenization, coating, and finally drying to obtain a 150 μm wet method positive electrode sheet;

[0130] The negative electrode active material graphite, the negative electrode conductive agent conductive carbon black (SP), the gel monomer diallyl carbonate, the initiator azobisisobutyronitrile (AIBN), the negative electrode binder styrene-butadiene rubber (SBR), and the negative electrode binder sodium carboxymethyl cellulose (CMC) are mixed evenly in a mass ratio of 95.2:1:2:0.2:1.5:0.1, and then the solvent pure water is added, and the wet slurry is applied, and finally dried to obtain a 120 μm wet-process negative electrode sheet; it should be noted that there are differences in the type and amount of binder used in the wet preparation of electrodes and the dry preparation of electrodes. At the same time, in order to ensure that the gel semi-solid battery prepared in this comparative example has the same capacity as the gel semi-solid battery prepared in Example 1 to be comparable, the amount of the negative electrode active material is also adjusted accordingly.

[0131] The remaining steps (b) and (c) are the same as in Example 1.

[0132] In order to compare the technical effects of the above embodiments and comparative examples, the following experimental examples are specially designed.

[0133] Experimental Example 1

[0134] The cells prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to ultrasonic testing. Figure 1 shown.

[0135] Depend on Figure 1 It can be seen that since Example 1 pre-mixed with gel monomer by a dry method, it is more uniform after curing than Comparative Example 1. Although Comparative Example 2 also pre-mixed with gel monomer, most of the gel was lost when the electrode was dried, so a small amount of unevenness would also occur.

[0136] Experimental Example 2

[0137] The gel semi-solid batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2 were selected for electrical performance testing, and their internal resistance, rate performance and cycle performance were tested respectively.

[0138] Internal resistance test method: At a temperature of 25°C, discharge at a constant current of 2C for 10s, and test the DCIR under different SOCs. The test results are as follows: Figure 2 and Figure 3 .

[0139] Rate performance test method: At a temperature of 25°C, constant current charging was performed at 0.2C, 0.33C, 0.5C, 1C, and 2C, and then constant current discharge was performed at a rate of 1C. The charge cut-off voltage was 3.65V, and the charge capacity retention rate at different rates was tested. The discharge cut-off voltage was 2.5V. The test results of the charge capacity retention rate at different rates are as follows: Figure 4 As shown; at a temperature of 25°C, the battery was charged at a constant current of 1C with a cut-off voltage of 3.65V, and then discharged at constant currents of 0.2C, 0.33C, 0.5C, 1C, and 2C with a cut-off voltage of 2.5V. The test results of the discharge capacity retention rate at different rates are shown as follows Figure 5 shown.

[0140] Cyclic performance test method: (1) 1C constant current and constant voltage charge to 3.65V, cut-off current 0.05C; (2) 1C constant current discharge, cut-off voltage 2.5V; (3) Cycle 8000 times; the test results of the first 1000 times are as follows Figure 6 shown.

[0141] from Figure 2-Figure 6 It can be seen from the data that compared with Comparative Examples 1 and 2, the DC internal resistance of Example 1 during the charge and discharge process is much lower, and its charge and discharge rate (especially at high rates) performance is also better than that of Comparative Examples 1 and 2.

[0142] In addition, Table 1 also lists the internal resistance, rate performance and cycle performance of each embodiment and comparative example under certain conditions, as follows:

[0143] Table 1

[0144]

[0145] Specifically, Examples 7-9 are comparative experiments of Example 1, which mainly examine the effect of the relative amount of gel monomer in the positive electrode plate on battery performance. From the data in Table 1, it can be seen that when the mass fraction of the gel monomer is too high (Example 8), the internal resistance of the battery cell becomes significantly larger, and the rate performance and cycle performance of the battery decrease significantly. If the mass fraction of the gel monomer is too low (Example 9), the entire battery system tends to be more liquid, and the electrical performance is improved, but the gel polymer formed by the reaction is too small to completely enclose the electrolyte, and there will be free electrolyte, which reduces the safety of the battery, which is mainly reflected in overcharging, extrusion, hot box, acupuncture, etc.

[0146] Examples 10 and 11 are also comparative experiments of Example 1, mainly investigating the effect of the relative amount of gel monomer in the gel electrolyte prepolymer on the battery performance. From the data in Table 1, it can be seen that when the mass fraction of the gel monomer is 1-10%, there is no significant difference in the electrical performance, indicating that the amount of gel monomer in this range is relatively reasonable, and while ensuring good safety, the electrical performance does not decrease significantly.

[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.

Claims

1. A method for preparing a gel semi-solid battery, characterized in that: The following steps are involved: (a) mixing a positive electrode active material, a positive electrode conductive agent, a gel monomer, an initiator and a positive electrode binder to form a positive electrode material, and then preparing a dry positive electrode sheet by using a dry electrode technology; The negative electrode active material, the negative electrode conductive agent, the gel monomer, the initiator and the negative electrode binder are mixed to form a negative electrode material, and then the negative electrode material is made into a dry negative electrode sheet by a dry electrode technology; (b) providing a gel electrolyte prepolymer formed by mixing a gel monomer, an initiator and an electrolyte; (c) Assembling the dry-process positive electrode plate and the dry-process negative electrode plate obtained in step (a) with a separator into a dry battery cell, injecting the gel electrolyte prepolymer obtained in step (b) into the dry battery cell and allowing it to stand for infiltration, and then heating for in-situ polymerization and curing to obtain a gel semi-solid battery.

2. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: In step (a), the positive electrode active material, the positive electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a positive electrode mixture; then the positive electrode binder is added to the positive electrode mixture, sheared and mixed to obtain a positive electrode material; then the positive electrode material is rolled into a film and compounded with a foil to obtain a dry-process positive electrode sheet.

3. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: In step (a), the negative electrode active material, the negative electrode conductive agent, the gel monomer and the initiator are stirred and mixed uniformly to obtain a negative electrode mixture; then the negative electrode binder is added to the negative electrode mixture, sheared and mixed to obtain a negative electrode material; then the negative electrode material is rolled into a film and compounded with a foil to obtain a dry-process negative electrode sheet.

4. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: In the dry-process positive electrode sheet, dry-process negative electrode sheet and gel electrolyte prepolymer, the gel monomer is a carbonate or acrylate organic reaction monomer, preferably including diallyl carbonate, propane trimethylol triacrylate, butyl methacrylate, methyl methacrylate, triethylene glycol dimethyl diacrylate, pentaerythritol tetraacrylate, pentaerythritol hexaacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, 2-bromoethyl acrylate, hydroxypropyl acrylate, isostearyl acrylate, methyl Any one or any combination of two or more of isobutyl acrylate, 4-hydroxybutyl acrylate, tributyltin acrylate, propane-1,3-diyl diacrylate, 4-ethylphenyl acrylate, hydroxyethyl acrylate, hydroxypentabromophenyl methacrylate, pentabromophenyl acrylate, 6-bromo-1-hexyl acrylate, 2-bromoethyl acrylate, 2-chloroethyl methacrylate, 11-undecylphosphonate, tributyltin acrylate or 2-(perfluorobutyl)ethyl acrylate; And / or, in the dry-process positive electrode sheet, the dry-process negative electrode sheet and the gel electrolyte prepolymer, the initiator includes an azo initiator or a peroxide initiator, preferably including at least one of azobisisobutyronitrile, diisopropylbenzene peroxide or dibenzoyl peroxide.

5. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: The positive electrode active material includes at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide; and / or, the negative electrode active material comprises at least one of graphite, silicon carbon, silicon oxygen or hard carbon; And / or, the positive electrode conductive agent and the negative electrode conductive agent are independently selected from at least one of Ketjen black, carbon nanotubes, two-dimensional transition metal carbon / nitride, acetylene black, Super P or graphene; And / or, the positive electrode binder and the negative electrode binder are independently selected from at least one of polytetrafluoroethylene, sodium carboxymethyl cellulose or polyethylene oxide; preferably, the negative electrode binder includes polytetrafluoroethylene, sodium carboxymethyl cellulose and polyethylene oxide.

6. The method for preparing a gel semi-solid battery according to any one of claims 1 to 5, characterized in that: Taking the mass fraction of the positive electrode material as 100%, the positive electrode material includes the following components in mass fractions: 85-95% positive electrode active material, 0.5-1.5% positive electrode conductor, 1-10% gel monomer, 0.05-1% initiator and 0.5-5% positive electrode binder.

7. The method for preparing a gel semi-solid battery according to any one of claims 1 to 5, characterized in that: Taking the mass fraction of the negative electrode material as 100%, the negative electrode material includes the following components in mass fractions: 85-95% of negative electrode active material, 0.5-1.5% of negative electrode conductor, 2-10% of gel monomer, 0.2-1% of initiator and 0.5-5% of negative electrode binder.

8. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: In step (b), gel monomer and initiator are added to the electrolyte and mixed evenly to obtain a gel electrolyte prepolymer; And / or, in step (b), based on the mass fraction of the gel electrolyte prepolymer being 100%, the gel electrolyte prepolymer comprises the following components in mass fractions: 89-98.95% electrolyte, 1-10% gel monomer and 0.05-1% initiator.

9. The method for preparing a gel semi-solid battery according to claim 1, characterized in that: In step (c), the standing and soaking time is 12 to 48 hours, and the standing and soaking temperature is 25 to 45° C.; And / or, the in-situ polymerization curing temperature is 50-80° C., the pressure is 0.3 MPa-1 MPa, and the curing time is 2-24 hours.

10. A gel semi-solid battery, characterized in that: The gel semi-solid battery is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of in-situ polymerization semi-solid battery

    CN115548456A

  • Gel electrolyte, semi-solid battery and preparation method

    CN116247288A

  • Gel polymer battery and preparation method thereof

    CN114388869A

  • Electrode slurry, electrode plate, preparation method of electrode plate, battery and preparation method of battery

    CN115148996A

  • Lithium battery positive and negative pole pieces prepared by dry method and preparation method of lithium battery positive and negative pole pieces

    CN115911280A

Cited By

  • Whole-domain integrated gel semi-solid battery and preparation method thereof

    CN120473574A

  • Method for preparing positive pole piece of lead-carbon battery by dry method, positive pole piece and battery

    CN120545317A

  • Semi-solid battery and preparation method thereof

    CN122291672A

  • Pole piece, preparation method thereof, electrochemical device containing pole piece and electronic equipment

    CN122348180A

  • A semi-solid lithium battery and a formation method thereof

    CN122739551A